Cardiac troponins in young marathon runners - Traiperm, N.; Gatterer, H.; Wille, M.; Burtscher, M. (The American Journal of Cardiology, 2012)
Cardiac troponin increases are common in adult marathon finishers. However, data on troponin values for young marathon runners are scarce. Forty young runners (20 healthy male and 20 female) 13 to 17 years old participated in this study. Blood samples were taken before, immediately after, and 24 hours after the race for determination of cardiac troponin T (cTnT) and troponin I (cTnI). Thirty-seven runners completed the race with a mean finishing time of 4 hours 53 minutes. No participant developed an adverse medical event during or after the race. In 30 of 37 participants, levels of cTnT and/or cTnI exceeded upper reference limits of 0.01 and 0.1 ng/ml immediately after the race, and in 3 participants these levels were even higher than the reference range for acute myocardial infarction (>0.1 and >0.5 ng/ml for cTnT and cTnI, respectively). Twenty-four hours after the race no participant had troponin levels exceeding the upper reference limits. Average increases of troponin levels did not differ between sexes. In conclusion, this is the first study to show that cardiac troponin levels increase to a similar extent in male and female adolescent marathon runners as observed in adults. Rapid recovery of troponin levels after a race is indicative of a physiologic rather than a pathologic response.